Effect of glucocorticoid therapy on adrenal function in children with acute lymphoblastic leukemia - Gita Widyapuri; Djajadiman Gatot; Aman Bakti Pulungan; Badriul Hegar (Paediatrica Indonesiana, 2014)
BackgroundGlucocorticoids play an important role in thetreatment ofacute lymphoblastic leukemia (ALL), but can causeside effects such as suppression of the hypothalamic-pituitaryadrenal (HPA) axis. Suppression of the HPA axis causes adrenal insufficiency, disturbs the cortisol response to stress, and may be a cause of morbidity and mortality in children with ALL.ObjectiveTo evaluate adrenal function in children with ALL afterinduction chemotherapy with high dose glucocorticoids.MethodsThe adrenal function of 20 children with ALL wasevaluated using a standard dose (250 Î¼ g) adrenocorticotropinhormone (ACTH) test performed before and after a 6 week oftreatment with glucocorticoids induction phase chemotherapy,which was followed by a week period tapering off. Adrenalinsuffien cy was defined as blood cortisol level of < 18 Î¼g/dLResultsAdrenal insufficiency was found in 14/20 subjects afterthe induction phase followed by a week period of tapering off.Median cortisol levels pre- and post-stimulation before inductionphase were 14.72 (range 2.0 1- 46. 1) Î¼g/dL and 29.29 (range 21.65 - 55 .15) Î¼g/dL, respectively. Median cortisol levels pre- and poststimulation after induction phase were 5.87 (range 0.2 - 20.53)Î¼g/dL and 10.49 (range 0.33 - 28.69) Î¼g/dL, respectively. Clinicalsigns and symptoms did not differ between those with and withoutadrenal insufficiency.ConclusionOf 20 children with ALL, 14 develop adrenalinsufficiency after a 6-week induction therapy with glucocorticoidsand followed by a week period of tapering off. No specific clinicalsigns and symptoms are identified to be related to the adrenalinsufficiency.